Multi- or Intergenerational Learning? Exploring Some Meanings. Issue 1 (2nd January 2017) - Watts, Jane
ABSTRACT: Through a previous project, I explored the community impact of a "family learning" intergenerational project. Throughout this work, the term intergenerational remained problematic, construed, as it so often is, in a rather narrow way to include merely two generations. I suggested that to increase levels of cohesion and empowerment and to reflect more accurately the reality of our communities, it could be better to focus on the concept of multigenerational working and learning, to bring together greater cross-community involvement. This article therefore explores multigenerational learning from a theory and practice perspective.